Analisis Pengaruh Kompetensi dan Kedisiplinan Tenaga Kesehatan terhadap Kepuasan Pasien Rawat Inap Puskesmas Jasinga Kabupaten Bogor Jawa Barat - Noor Alya; Wahyuddin Latunreng (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2021)
Inpatients at the Jasinga Health Center in Bogor Regency have not met expectations. The purpose of the study: to analyze the effect of competence and discipline of health workers on the satisfaction of inpatients at the Jasinga Health Center, Bogor Regency, West Java. The framework of this research uses Competency Theory from Spencer and Spencer (Priansa, 2014: 258), Discipline Theory from Rivai and Sagala (2011: 825), and Goal theory from Lovelock (Latunreng, 2012: 152). Methods: This research uses quantitative research with an explanatory approach. Data analysis used the IBM SPSS Statistics Version 24 Program. Research Population The population in this study were recipients of inpatient services at the Jasinga Health Center from January to December 2019 as many as 781 patients, with Slovin (5%) getting 265 respondents. The sampling technique used accidental sampling. The results of the study: First, the positive and significant effect on the activities of inpatients at the Jasinga Health Center, Bogor Regency, West Java, with a regression equation test the magnitude of the effect is 0.997. Second, there is a positive and significant effect of the discipline of health workers on inpatients at the Jasinga Health Center, Bogor Regency, West Java, with a regression equation test the magnitude of the effect is 0.253. Third, there is a positive and significant effect of Competence and Discipline of Health Workers together on Inpatients at the Jasinga Health Center, Bogor Regency, West Java, with the magnitude of the influence of Competence and Discipline of Health Workers together on Inpatients at the Jasinga Health Center, Bogor Regency, West Java, reaching 0,789.